STUDI LITERATUR DAMPAK BUDAYA ORGANISASI PADA PERUSAHAAN MULTINASIONAL - Aditya Anwar Himawan (Universitas Jember, 2015)
Companies must be prepared to face the global competition, and organizational culture to support the success of the company. This journal aims to determine the impact of organizational culture in multinational companies. In addition, this study makes it possible to understand the aspects of labor productivity is influenced by the culture of the organization. This study used a qualitative descriptive approach with data collection using the study of literature is to collect data relating to the organizational culture in multinational companies originating from research journals. The research concludes that the existing organizational culture in multinational companies turned out to have a very important contribution in creating effective organizations support the success of the organization.